A microstructural and damage investigation into the effect of coiling temperature on the low temperature impact behaviour of an HSLA structural steel. (2nd January 2021) - Wu, S.; Bardelcik, A.; Zhou, T.; Badgley, P.; Cathcart, C.
ABSTRACT: An HSLA grade of structural steel was hot rolled using a coiling temperature of 500°C (CT500) or 540°C (CT540). As expected, the lower coiling temperature resulted in a more refined ferrite grain structure and a more dispersed distribution of smaller pearlite grains and carbides which formed along grain boundaries. Instrumented Charpy V-notch (CVN) tests were conducted and the CT500 material resulted in a higher ductile-brittle transition temperature, which was unexpected for the more refined microstructure. Damage evolution was characterized from the tested CVN specimens and revealed that a higher initial void/inclusion content for CT500 resulted in elevated void area fraction and void density values near the fracture surface of this material. Also, the refined distribution of carbides contributed to the higher void nucleation rate of CT500, which ultimately reduced the low temperature impact performance of this material.